2020
DOI: 10.1159/000510469
|View full text |Cite
|
Sign up to set email alerts
|

Falls and Fall-Related Consequences among Older People Living in Long-Term Care Facilities in a Megacity of China

Abstract: <b><i>Introduction:</i></b> Falls are currently the top safety problem in long-term care facilities (LTCFs) in China. Due to the increasing number of residents living in LTCFs, more evidence is needed to give a foundation for fall prevention. <b><i>Objective:</i></b> This study aimed to explore the epidemiological characteristics of falls in LTCFs in central Shanghai. <b><i>Methods:</i></b> The study was conducted in 21 LTCFs in a central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
2
0
2
Order By: Relevance
“…The locations and types of injuries we observed were aligned to previous reports on injuries from falls by older adults who reside in LTC [ 41 44 ] and in the community [ 45 , 46 ]. A Finnish LTC study [ 41 ] reported injuries in 38.1% of falls, including head injuries in 19.3% of falls, and fractures in 3.1% of falls, most often to the hip (1.5% of falls).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The locations and types of injuries we observed were aligned to previous reports on injuries from falls by older adults who reside in LTC [ 41 44 ] and in the community [ 45 , 46 ]. A Finnish LTC study [ 41 ] reported injuries in 38.1% of falls, including head injuries in 19.3% of falls, and fractures in 3.1% of falls, most often to the hip (1.5% of falls).…”
Section: Discussionsupporting
confidence: 81%
“…In studies of falls in Swedish [ 43 ] and Bavarian [ 42 ] nursing homes, injuries occurred in approximately 25% of falls, with the latter reporting hospitalizations in 7.6% of falls in common spaces. Bruising/hematoma, followed by abrasions/cuts, were the most commonly reported injuries from falls in community-dwelling older adults in the Netherlands and United States [ 45 , 46 ], and in LTC facilities in Sweden and China [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…12,15 In addition, "not vocalizing reciprocal exchanges at will" and always "waking at midnight" were predictors of PF decline. Falls, which are often directly related to PF decline, are more likely to occur at night, 26 primarily owing to insufficient lighting and a limited number of nursing home staff. Because those with cognitive impairment and communication difficulty are unable to ask for help, staff may not notice anything unusual, leading to falls and other adverse events that may cause PF decline.…”
Section: Discussionmentioning
confidence: 99%
“…Considera-se que as incidências de quedas são um caso de saúde pública, pois podem resultar em lesões (como hematomas, cortes ou escoriações), fraturas, redução na capacidade funcional, hospitalizações, prejuízos psicológicos (como o medo de sofrer novas quedas), podendo culminar em óbitos (Teixeira et al, 2019;Jiang et al, 2020). De acordo com Carlini Junior et al (2021), a incidência de quedas pode afetar cerca de 20% -30% dos idosos com mais de 60 anos e a partir dos 75 anos ela aumenta 5%, resultando em fraturas ou hospitalizações.…”
Section: Introductionunclassified